STAKEHOLDERS ANALYSIS IN COMMUNITY-BASED SUSTAINABLE TOURISM DEVELOPMENT IN BLIMBINGSARI TOURISM VILLAGE, JEMBRANA REGENCY, BALI - Cinahya Winursita, Mirmanti
Blimbingsari Tourism Village has a unique acculturation of Balinese Hindu culture and Protestant Christianity which makes Community Based Tourism (CBT) an approach to tourism development. The emphasis on CBT requires the pentahelix collaboration to optimize the benefits of tourism in economic, social and environmental aspects. This study aims to identify stakeholders’ characteristics and their relationships in community-based sustainable tourism development. Stakeholder Analysis Matrix and Social Network Analysis are used in this study based on the results of semi-structured interviews and literature review to examine the characteristics, in the form of knowledge, strengths, interests, and influence of each stakeholder, and their relationships within the pentahelix collaboration framework. This study found that stakeholder knowledge of the definition of CBT was high with the various contributions of each stakeholder. Stakeholder strength in implementing CBT is divided based on authority, availability, and ability to mobilize resources, as well as leadership in accordance with the main tasks, functions, and authority they have. It was found that the Pemerintah Desa Blimbingsari, Pokdarwis, and Balai TNBB have very significant strengths and support the implementation of CBT in Blimbingsari Village. Stakeholder interests in the form of involvement, alliances, and the impact of CBT have resulted that all stakeholders supporting CBT as evidenced by involvement according to authority, perceived benefits, and obstacles that are considered as challenges in implementing CBT. The influence of stakeholders represented by their knowledge, strengths, and interests is varied but specific. Inter-stakeholder relationships vary in type, direction, and intensity according to the characteristics of the stakeholders. Institutions at the local scale have the most diverse types of relationships. Based on the characteristics and relationships that occur, four strategies for increasing stakeholder involvement are formulated which are detailed using a community capacity strategy approach, innovation and the role of government institutions, as well as an institutional synergy approach.